Stories about Values and Valuable Stories: A Field Experiment of the Power of Narratives to Shape Newcomers’ Actions - Martin, Sean R. (Academy of Management Journal, 2016)
This study draws on social identity theories of behavioral contagion and research concerning narratives in organizations to present and test a framework for understanding how narratives embed values in organizational newcomers’ actions. Employing a field experiment using newly hired employees in a large IT firm that prioritizes self-transcendent values, this study explores how narratives that vary in terms of the organizational level of main characters and the values-upholding or values-violating behaviors of those characters influence newcomers’ tendencies to engage in behaviors that uphold or deviate from the values. The results indicate that stories about low-level organizational characters engaging in values-upholding behaviors are more positively associated with self-transcendent, helping behaviors, and negatively associated with deviant behaviors, than are similar stories about high-level members of the organization. Stories in which high-level members of the organization violate values are more strongly negatively related to newcomers’ engagement in both helping and deviance than are values-violating stories about lower-level members. Content analyses of the stories suggest that they convey values in different and potentially important ways. Implications, future directions, and limitations are discussed.